2021
DOI: 10.1186/s12931-021-01760-6
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic pulmonary fibrosis and diabetes mellitus: a meta-analysis and systematic review

Abstract: Background Idiopathic pulmonary fibrosis (IPF) is a chronic diffuse interstitial lung disease, of which the etiology has been poorly understood. Several studies have focused on the relationship between IPF and diabetes mellitus (DM) in the past years but have failed to reach a consensus. This meta-analysis aimed to examine the association between diabetes to IPF. Methods We accumulated studies investigating the association between DM and IPF from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 59 publications
0
23
1
Order By: Relevance
“… 24 25 There is an association between DM and ILD/IPF with an unknown mechanism. 26 Our study has shown that DM with end-organ damage increased RA-ILD mortality. Further study is needed to explore the pathophysiology linkage between DM and RA-ILD.…”
Section: Discussionmentioning
confidence: 57%
“… 24 25 There is an association between DM and ILD/IPF with an unknown mechanism. 26 Our study has shown that DM with end-organ damage increased RA-ILD mortality. Further study is needed to explore the pathophysiology linkage between DM and RA-ILD.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, the clinical effectiveness of MET in patients with PF should be combined with ongoing studies on PF-specific biomarkers ( Raghu et al, 2018 ). 3) PF may not be clinically isolated, often existing in combination with other diseases, and may be influenced by factors such as smoking, age, and sex of the patient, suggesting that confounding factors often influence these studies ( Bai et al, 2021 ). This may be the reason for some bias in the studies and the impact of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia causes inflammation and oxidative stress in the body, which are closely related to the core developmental mechanisms of PF, such as extracellular matrix (ECM) deposition, fibroblast/myofibroblast proliferation, and structural disruption of the lung tissue ( Willis & Borok, 2007 ). Similarly, in a meta-analysis, a significant increase in the prevalence of DM was demonstrated in patients with IPF compared with that in controls, suggesting a potential positive association between DM and the development of IPF ( Bai et al, 2021 ).…”
Section: Introductionmentioning
confidence: 93%
“…The relatedness of IPF to diabetes is another finding worth discussion. There are several clinical studies including clinical meta analyses suggesting an association between IPF and diabetes [31][32][33][34] . Our computational study also indicates molecular relatedness of IPF to diabetes (Fig.…”
Section: Pre-clinical and Clinical Evidencementioning
confidence: 99%